2022
DOI: 10.3390/children9111608
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Bracing Treatment on Static and Dynamic Baropodometric Parameters in Adolescent Idiopathic Scoliosis

Abstract: Postural balance is an important but not well-studied concept in the treatment of adolescent scoliosis. The aim of this study was to assess whether conservative treatment with Sforzesco bracing induced negative perturbations on postural stability, as related to static, postural, and dynamic baropodometric indicators. Twelve subjects (12 females, aged 11–16) with moderate AIS, were selected among a group of 97 patients. Inclusion criteria were: (1) confirmed diagnosis of moderate AIS (Cobb angle of 21° to 35° f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Three studies [ 34 , 37 , 47 ] investigated the effect of scoliosis treatments on balance control. Pavone et al and Kavyani et al [ 34 , 47 ] investigated the short-term effects of wearing a brace on postural control in a quiet standing position.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies [ 34 , 37 , 47 ] investigated the effect of scoliosis treatments on balance control. Pavone et al and Kavyani et al [ 34 , 47 ] investigated the short-term effects of wearing a brace on postural control in a quiet standing position.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies [ 34 , 37 , 47 ] investigated the effect of scoliosis treatments on balance control. Pavone et al and Kavyani et al [ 34 , 47 ] investigated the short-term effects of wearing a brace on postural control in a quiet standing position. The results showed that braces did not improve balance in subjects with AIS, but rather increased the sway speed of the COP [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment of pediatric spinal deformities depends on their etiology. The gold standard in the treatment of idiopathic scoliosis is rehabilitation and corset treatment, and in the case of curvature progression despite the treatment above of over 50 degrees, Cobbsurgical treatment [15,16]. In the case of congenital scoliosis with vertebral segmentation disorders, conservative treatment and a brace do not tend to have a significant impact on the development of curvature, and surgical treatment is recommended [17].…”
Section: Discussionmentioning
confidence: 99%
“…In mild spinal curves, treatment is based on rehabilitation with physical therapy. In moderate cases, spinal bracing is the standard method and the most widely used approach to correct spinal deformity and prevent the progression of the scoliosis [2][3][4]. Patients with a Cobb angle greater than 40 degrees often require surgical treatment, and various surgical systems may be applied to correct the spinal deformity [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%